2016
DOI: 10.1002/mc.22563
|View full text |Cite
|
Sign up to set email alerts
|

S100A6 promotes cell proliferation in human nasopharyngeal carcinoma via the p38/MAPK signaling pathway

Abstract: An elevated level of S100A6 is associated with poor outcomes of many tumor types, but, how S100A6 contributes to nasopharyngeal carcinoma (NPC) progression remains unknown. Here, we investigated the expression and prognostic significance of S100A6 in NPC and explored the molecular mechanisms under-lying the role of S100A6 in NPC development. The results showed that S100A6 was markedly up-regulated in NPC tissues and cell lines compared to paired peritumoral normal tissues and a normal nasopharyngeal epithelial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 37 publications
3
20
0
Order By: Relevance
“…p38 can be activated by tyrosine kinase receptors (PDGF receptor, VEGF receptor, EGF receptor, FGFR1) to function as a positive regulator of tumor progression, mediating motility and invasion, suppressing apoptosis, stimulating the epithelial‐to‐mesenchymal transition in various cell types (Bates & Mercurio, ; Frey et al , ; Nishihara et al , ). Our results demonstrating that p38α promotes proliferation, by upregulating MYC mRNA levels are in line with the protumorigenic functions of p38 and with recent studies in breast, head and neck cancers and nasopharyngeal carcinoma (Leelahavanichkul et al , ; Li et al , ; Wada et al , ). The activation of p38 by activated‐FGFR3 in bladder tumors contributes to malignant behavior and the inhibition of this activation may be of therapeutic value, as reported for an increasing number of cancers (Koul et al , ; Igea & Nebreda, ).…”
Section: Discussionsupporting
confidence: 92%
“…p38 can be activated by tyrosine kinase receptors (PDGF receptor, VEGF receptor, EGF receptor, FGFR1) to function as a positive regulator of tumor progression, mediating motility and invasion, suppressing apoptosis, stimulating the epithelial‐to‐mesenchymal transition in various cell types (Bates & Mercurio, ; Frey et al , ; Nishihara et al , ). Our results demonstrating that p38α promotes proliferation, by upregulating MYC mRNA levels are in line with the protumorigenic functions of p38 and with recent studies in breast, head and neck cancers and nasopharyngeal carcinoma (Leelahavanichkul et al , ; Li et al , ; Wada et al , ). The activation of p38 by activated‐FGFR3 in bladder tumors contributes to malignant behavior and the inhibition of this activation may be of therapeutic value, as reported for an increasing number of cancers (Koul et al , ; Igea & Nebreda, ).…”
Section: Discussionsupporting
confidence: 92%
“…Early reports have indicated that MAPK and PI3K pathways are targets for the development of therapeutic agents against nasopharyngeal carcinoma . Recently, S100A6 has been shown to elevate cell proliferation by increasing the levels of the phosphorylated p38 pathway in human nasopharyngeal carcinoma patients . In agreement with this finding, we also observed upregulation of p38 and JNK1/2 phosphorylation in licochalcone A‐treated HONE‐1 cells.…”
Section: Discussionsupporting
confidence: 91%
“…47 Recently, S100A6 has been shown to elevate cell proliferation by increasing the levels of the phosphorylated p38 pathway in human nasopharyngeal carcinoma patients. 48 In agreement with this finding, we also observed upregulation of p38 and JNK1/2 phosphorylation in licochalcone A-treated HONE-1 cells. The inhibitor of JNK1/2 or p38 significantly attenuated the licochalcone A-induced protein expression of cleaved-caspase-9, cleaved-caspase-8, and cleaved-caspase-3.…”
Section: Discussionsupporting
confidence: 90%
“…4B). MAPK (p38) pathway plays a crucial role in cell proliferation and metastasis, the inflammatory microenvironment in cancers [22][23][24][25]. In neurological diseases, CTSC was found to induce microglia M1 polarization and promote neuroinflammation via activation of protein kinase C/p38-MAPK/nuclear factor-#B pathway [26].…”
Section: Discussionmentioning
confidence: 99%